(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Artemisia vulgaris L. (Artemisia V.) has a great role in treatment of many diseases like gastrointestinal diseases, inflammation and fungal infections. Other important activity is antioxidant which put this plant as a good choice to reduce liver toxicity. In this study, the hepatoprotective effect of Iraqi Artemisia vulgaris L. against the liver toxic chemotherapy cisplatin were determined in mice.Methods: Two different doses of Iraqi Artemisia vulgaris L. extract were given to mice with and without cisplatin as a liver toxicity inducer. The blood level of liver enzymes ALT, AST, ALP and TSB were measured.Results: The elevation in blood level of liver enzymes reduced significantly in pre-treated mice with Artemisia extracted (200 and 400 mg/ Kg) and cisplatin, compared with mice group that received cisplatin alone.Conclusion: Hepatoprotective activities of Artemisia vulgaris L. extract were confirmed, and 400 mg/kg/day the extract was the most effective dose. This finding provides scientific evidence for the use of safe medicinal herbs such as A. vulgaris in the treatment of liver toxicity produced by other medications such as chemotherapy.